(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the processes of civil society formation in Uzbekistan on the eve of independence within the context of political, social, and economic conditions. It examines the fundamental changes in the public administration system, challenges encountered during the transition from a totalitarian system to a democratic society, and factors influencing the development of civil society institutions. Through comparative analysis with Western European countries, both common and unique aspects of Uzbekistan’s transition period are identified. The impact of normative legal acts adopted after independence, particularly laws, decrees, and resolutions, on the development of civil society is explored. Additionally, the article analyzes reforms aimed at enhancing public oversight and strengthening cooperation between non-governmental organizations and the state. The effectiveness of civil society institutions is evaluated using modern indices.